2016
DOI: 10.1007/s00784-016-1844-x
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue coverage on the segmentation accuracy of the 3D surface-rendered model from cone-beam CT

Abstract: ObjectivesThe aim of this study is to investigate the effect of soft tissue presence on the segmentation accuracy of the 3D hard tissue models from cone-beam computed tomography (CBCT).Materials and methodsSeven pairs of CBCT Digital Imaging and Communication in Medicine (DICOM) datasets, containing data of human cadaver heads and their respective dry skulls, were used. The effect of the soft tissue presence on the accuracy of the segmented models was evaluated by performing linear and angular measurements and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…First of all, the present series of medical imaging scans in vitro prevented realistic reconstruction of physiological loading conditions. In addition, the use of a single specimen and the manual segmentation procedure, though performed by a single operator, could have influenced the quality the final anatomical 3D models (57), in particular for the calculation of the talar parameters for prosthesis design. The present preliminary repeatability analysis shows that the observations are maintained also for other processing sessions of the same operator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the present series of medical imaging scans in vitro prevented realistic reconstruction of physiological loading conditions. In addition, the use of a single specimen and the manual segmentation procedure, though performed by a single operator, could have influenced the quality the final anatomical 3D models (57), in particular for the calculation of the talar parameters for prosthesis design. The present preliminary repeatability analysis shows that the observations are maintained also for other processing sessions of the same operator.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the quality of these single and combined models also after these registration procedures, DMA was used as surface-to-surface analysis, performed by '3D compare' tool in Geomagic Control (48,57). In this tool, the '3D deviation' type was set, for which the shortest distance from each point on one surface (the 'Test') to any point on the other (the 'Reference') is reported as the result.…”
Section: Dmamentioning
confidence: 99%
“…In this in vitro study, the use of the human dry skull without a soft tissue substitute may involve a drawback, as it does not simulate the actual anatomy in a real clinical situation. Dusseldorp et al investigated the effect of soft tissue presence on the 3D image segmentation accuracy of hard tissue models from CBCT and concluded that, although the soft tissue presence appears to affect the accuracy of the 3D hard tissue model obtained from a CBCT scanner, discrepancies were below a generally clinical acceptable level of 1 mm [ 35 ]. Further studies should investigate how to optimize parameter settings to overcome the potential inaccuracy of image matching between CBCT and optical dental scan images in patient-based clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…11 From their results, the underestimation caused by the CBCT is approximately 70% for thinner alveolar bone (thickness < 0.72 mm). Moreover, factors such as soft tissue coverage, 12 the bias of different doctors, and patients’ posture could result in the tendency difference of CBCT measurements. Therefore, the CBCT measurement errors are caused by a variety of factors and are difficult to avoid.…”
Section: Introductionmentioning
confidence: 99%